The role of athletic identity in the development of athlete burnout: The moderating role of psychological flexibility. (November 2018) - Chang, Wen Hsin; Wu, Chia-Huei; Kuo, Che-Chun; Chen, Lung Hung
Abstract: Inconsistent findings have been reported regarding the association between athletic identity and emotional exhaustion, a key dimension of athlete burnout, indicating a need to identify boundary conditions that shape the role of athletic identity in the development of emotional exhaustion. To reconcile the mixed findings, the authors propose that psychological flexibility, identified as "the ability to contact the present moment more fully as a conscious human being and to change or persist in behavior when doing so serves valued ends" (Hayes, Luoma, Bond, Misuka, & Lillis, 2006, p. 8), can moderate the association between athletic identity and the development of emotional exhaustion. Using a two-wave, time-lagged survey, a total of 132 college athletes (mean age = 19.97 years) completed assessments of athletic identity at Time 1, psychological flexibility at Time 1, and emotional exhaustion at Time 1 and at Time 2 three months later. The results indicated that athletic identity is positively associated with the development of emotional exhaustion over time among individuals with low psychological flexibility but is negatively associated with emotional exhaustion for individuals with high levels of psychological flexibility. This study suggests that the association of athletic identity with increased or decreased emotional exhaustion over time depends on the athlete's attributes. Practically, our findings highlight the importance of understanding athletes' levels of psychological flexibility to prevent emotional exhaustion. Highlights: We examine psychological flexibility as a moderator of athletic identity and athlete burnout relationship. Athletic identity did not accounted for changes in emotional exhaustion independently. Psychological flexibility significantly moderates the association between athletic identity and emotional exhaustion over time.